Anomalous Corrosion of Bulk Transition Metal Diselenides Leading to Stable Monolayers - Huang, Yu-Ting; Dodda, Akhil; Schulman, Daniel S; Sebastian, Amritanand; Zhang, Fu; Buzzell, Drew; Terrones, Mauricio; Feng, Shien-Ping; Das, Saptarshi (ACS applied materials & interfaces, 2017)
In this paper we provide insight into an anomalous corrosion process, referred to as electroablation (EA), which converts multilayer flakes of transition metal diselenides like MoSe2 into their corresponding monolayers when micromechanically exfoliated on a conductive electrode and subsequently subjected to a high anodic potential inside a conventional electrochemical cell. Photoluminescence intensity maps and scanning transmission electron microscopy (STEM) images confirmed the single crystalline nature and 2H-hexagonal lattice structure of the remnant monolayer MoSe2 flakes, indicating the superior corrosion stability of the monolayers compared to that of the bulk counterpart. It is noted that the EA technique is a low-cost alternative for high-yield synthesis of single crystalline monolayer MoSe2 at room temperature. We also found that the dynamics of such an electro-oxidation-mediated and self-limiting corrosion process differs significantly for MoSe2 and WSe2. While we were able to engineer the corrosion conditions for the EA process to obtain monolayers of MoSe2, our attempts to obtain monolayers of WSe2 were largely unsuccessful. Finally, we constructed a phenomenological physical chemistry framework to explain such anomalous corrosion processes in transition metal diselenides.